W sprawie zasadności dualizmu sądownictwa w sprawach własności przemysłowej - Dobieżyński, Krzysztof (PRAWO i WIĘŹ, 2025)
The subject of this paper is an attempt to answer the question of whether all cases heard by administrative courts, particularly those relating to industrial property, should be transferred to the jurisdiction of civil courts. Such proposals are still being put forward in legal theory. Supporters of this solution argue that litigation proceedings previously examined by the Patent Office of the Republic of Poland, in particular, should be transferred in their entirety to civil courts. Therefore, the current state of industrial property jurisdiction, including the establishment of intellectual property courts, will be discussed. Furthermore, the arguments for and against introducing the above solution to control of decisions of the Patent Office will be analysed.